Outcome of 82 chronic myeloid leukemia patients treated with nilotinib or dasatinib after failure of two prior tyrosine kinase inhibitors - Rossi, A. R.; Breccia, M.; Abruzzese, E.; Castagnetti, F.; Luciano, L.; Gozzini, A.; Annunziata, M.; Martino, B.; Stagno, F.; Cavazzini, F.; Tiribelli, M.; Visani, G.; et al. (Haematologica (Roma), 2013)
There have been few reports of a response to dasatinib or nilotinib after failure of two prior sequential tyrosine kinase inhibitors. We report the outcome of 82 chronic phase patients who received nilotinib or dasatinib as third-line alternative tyrosine kinase inhibitor therapy. Thirty-four patients failed to respond to nilotinib and were started on dasatinib as third-line tyrosine kinase inhibitor therapy while 48 patients were switched to nilotinib after dasatinib failure. Overall, we obtained a cytogenetic response in 32 of 82 patients and major molecular response in 13 patients; disease progression occurred in 12 patients. At last follow up, 70 patients (85.4%) were alive with a median overall survival of 46 months. Our results show that third-line tyrosine kinase inhibitor therapy in chronic myeloid leukemia patients after failure of two prior sequential tyrosine kinase inhibitors may induce a response that, in some instances, could prolong overall survival and affect event-free survival.